(untitled) (Raparin Journal of Humanities (RJH), 2025)
The expectation gap between auditors’ performance and the demands or expectations of financial statement users is a persistent and widespread issue in the external auditing profession, both globally and locally. This gap has been extensively studied, evaluated, and analyzed by various committees, organizations, and researchers worldwide. It challenges the credibility of the auditing profession and can sometimes lead to conflicts. The Kurdistan Region is not immune to this issue, with frequent disputes arising between auditors and beneficiaries, particularly tax authority. This research aims to analyze and evaluate the expectation gap between auditors’ performance and the desires of financial statement users. It seeks to propose solutions to bridge this gap, thereby enhancing the quality of the auditing profession and ensuring the provision of highly credible financial statements in the Kurdistan Region. The study concludes that several factors contribute to narrowing this expectation gap. These include auditors’ adherence to auditing standards, their responsibility for detecting errors and fraud, and the awareness level of financial statement users regarding auditors’ roles and objectives. Improving these aspects can significantly enhance the quality of auditing. The research also emphasizes the need for auditors to improve their professional performance to meet users’ expectations and the importance of implementing both local and international auditing standards. To bridge the expectation gap between auditors’ performance and the desires of financial statement users, it can be recommended that enhanced Communication Improve communication between auditors and financial statement users to clarify the scope and limitations of the audit process.